Aplicación de la contabilidad de costos por ordenes de producción en la imprenta Easyprint de la ciudad de Loja en el periodo agosto-septiembre 2014 - Jaramillo Lima, Ximena Beatriz (2015)
The subject of this investigation "APPLICATION OF ACCOUNTING ORDERS PRODUCTION COSTS IN THE CITY EASYPRINT LOJA PRINTING IN AUGUST-SEPTEMBER 2014 PERIOD" main objective is to design and establish a model or system costs aimed at improving the speed and reliability of the information on production costs and more viable administration. He met the objectives by implementing a system of cost accounting for production orders in the company "Printing EASYPRINT" which allow, record, collect and report production costs (materials, labor and manufacturing overhead costs ) allowing to generate timely, valid and reliable information on the determination of product cost, inventory valuation, pricing and determination of profit, by generating financial statements. With accounting practice, the budget indirect costs of manufacturing and distribution fee for each production order was made, they were designed and used documents and records for the effective control of cost elements. It is concluded that the implementation of cost accounting for production orders where it was determined how much it cost to produce in the printing industry, the costs incurred during production. So the use of this accounting tool that provides timely and reliable information on the financial situation of the company which will allow its owner to make decisions or actions that promote the reduction of unnecessary costs in production is recommended